Effect of Enzyme Location on Activity and Stability of Trypsin and Urease Immobilized on Porous Membranes by Using Layer-By Self-Assembly of Polyelectrolyte - Guedidi, Sadika; Yürekli, Yılmaz; Yemenicioğlu, Ahmet; Deratani, André; Déjardin, Philippe; Alsoy Altınkaya, Sacide; Innocent, Christophe; Alsoy Altınkaya, Sacide; Roudesli, Sadok; Yemenicioğlu, Ahmet (Elsevier Ltd., 2010)
The layer-by-layer (LbL) self-assembly of polyelectrolyte is one of the simplest ways to immobilize enzyme on membrane. In this paper, the immobilization of trypsin (TRY) and urease (URE) on polyacrylonitrile based membranes using the LbL assembly technique was presented. The studied systems consisted in bilayered assemblies with the enzyme layer as the outer layer and trilayered assemblies with the enzyme layer as the inner sandwiched layer. The membrane pore size was chosen so that the smaller enzyme TRY was mainly immobilized within the membrane and confined in the porous membrane structure while URE immobilization mainly took place at the membrane surface. No dramatic difference on reactivity was evidenced between these two enzyme locations. The catalytic activity of immobilized enzymes was found to be lower than the free ones in solution but their stability was dramatically enhanced. The higher activity was observed when the enzyme is deposited as the outer layer of the LbL assembly. On the other hand, the more stable catalytic membranes were obtained when the outer layer consists of a polyelectrolyte covering the enzyme layer. © 2010 Elsevier B.V.
Keywords: Enzyme immobilization; Catalytic membrane; Layer-by-layer self-assembly; Polyelectrolytes